AN INVESTIGATION INTO THE CONCEPTUAL UNDERSTANDING OF STUDENTS ABOUT THE CONTENT OF EVS AT THE PRIMARY LEVEL - Sharma, S.V.; Yadav, S.; Niwas, R.; Horo, A.; Pratap, R. (SCHOOL SCIENCE, 2014)
An investigation into the conceptual understanding of content of EVS at the Primary level has been carried out in 10 sample schools. Three schools were English medium and seven schools were Hindi medium from both rural and urban areas in Ajmer district of Rajasthan. Investigators observed the classroom transactions of the content of EVS of the sample schools and administered the research tools on students and teachers. Investigators also interviewed the subject teachers to seek specific information in relation to their academic and professional qualifications as well as classroom transaction. Analysis of the data was done through both qualitative and quantitative approaches indicates that there is a considerable difference in conceptual understanding of EVS between the two groups of students: those who were studying in Hindi-medium schools and those who were studying in English-medium schools.